Pengaruh Latihan Jump Box Terhadap Hasil Kemampuan Three Point Shoot Pemain Bolabasket - Sartika, Dwi; Bayu, Wahyu Indra; Aryanti, Silvi (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
This study aims to determine the effect of jump box training on the results of three-point shoots for extracurricular basketball students at SMA Negeri 1 Martapura. The method used in this research is an experiment. The research design used was the One Group Pretest-Posttest Design. This sample was taken using a total population sampling technique with a total sample of 39 students. The research instrument was the three-point shoot test. From the results of data management and analysis using the data normality test and hypothesis testing with the T-test formula, jump box training has an effect on increasing the results of three-point shoots in basketball games. This can be seen from the results of data analysis through the calculation of the t-test formula with the criteria t count is greater than t table (13.730 ˃ 1.70) with a confidence level of 0.95 (α = 0.05) and the number of samples (N = 30). Jump box training can have an effect on increasing the results of three-point shoots for basketball extracurricular students at SMA Negeri 1 Martapura.